The Effect of Shading Devices on the Energy Consumption of Buildings: A Study on an Office Building in Dubai - Yassine, Farah (2013)
The world is witnessing a global movement working towards the goal of decreasing emissions that are causing the global warming phenomenon. The United Arab Emirates is striving to mitigate the effects of global warming by launching numerous initiatives that contribute to reducing emissions. One of the main sources of these emissions in the UAE is the buildings where the cooling loads required by buildings in Dubai accounts for 60% of the summer peak electricity load. Thus it is important to propose solutions to decrease energy consumptions of these buildings. Therefore, this study aims to quantify the potential energy savings achievable by external shading devices.